2015
DOI: 10.1007/s12565-015-0272-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nNOS in the human larynx

Abstract: Although intrinsic laryngeal neurons and ganglia have been studied in various species, they have been overlooked in humans. We aimed to investigate the presence of intrinsic laryngeal neurons in humans and, if present, to analyze their neuronal nitric oxide synthase (nNOS) expression. An immunohistochemical study using anti-nNOS antibodies was performed on samples obtained from four cadavers. Intrinsic laryngeal nNOS+ neurons were assessed in the submucosal layer, but nNOS+ nerves were found in all histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, Moncada et al ( 25 ) and other studies ( 63 , 64 ) have demonstrated that NO-mediated vasodilation occurs without endothelial cells present, where the NO-positive nitrergic nerves may act directly on smooth muscle cells, leading to vasodilation. Such control by neuronal NO has also been demonstrated in the peripheral nervous system ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 79%
“…However, Moncada et al ( 25 ) and other studies ( 63 , 64 ) have demonstrated that NO-mediated vasodilation occurs without endothelial cells present, where the NO-positive nitrergic nerves may act directly on smooth muscle cells, leading to vasodilation. Such control by neuronal NO has also been demonstrated in the peripheral nervous system ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 79%